2023
DOI: 10.1039/d2dt03765c
|View full text |Cite
|
Sign up to set email alerts
|

A bioinspired polydopamine–FeS nanocomposite with high antimicrobial efficiency via NIR-mediated Fenton reaction

Abstract: Ferrous and sulfur ion are the essential element for human body, which play an active role in maintaining the body's normal physiology. Meanwhile, the mussel-inspired polydopamine (PDA) possesses good hydrophilicity...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
(67 reference statements)
1
6
0
Order By: Relevance
“…This shift suggests the occurrence of intermolecular interactions between the CuS NPs and the electronegative nitrogen of PANI, implying a structural and chemical influence of PANI on the CuS matrix. Moreover, the characteristic spectrum observed in the composite also indicates a physical ordering and aligned conformation of the nanostructured polymer matrix, 65 which correlates with the findings from the XRD study. Additionally, it is also evident from the CuS@PANI spectrum that the absorption peak corresponding to the NH band in the NCs has shifted to a higher frequency range (specifically, 3303 to 3329 cm −1 ) with a sharper peak.…”
Section: Resultssupporting
confidence: 79%
“…This shift suggests the occurrence of intermolecular interactions between the CuS NPs and the electronegative nitrogen of PANI, implying a structural and chemical influence of PANI on the CuS matrix. Moreover, the characteristic spectrum observed in the composite also indicates a physical ordering and aligned conformation of the nanostructured polymer matrix, 65 which correlates with the findings from the XRD study. Additionally, it is also evident from the CuS@PANI spectrum that the absorption peak corresponding to the NH band in the NCs has shifted to a higher frequency range (specifically, 3303 to 3329 cm −1 ) with a sharper peak.…”
Section: Resultssupporting
confidence: 79%
“…The time constants (τ) for heat transfer of the system were calculated to be 487.1 and 458.5, respectively (Figure f,g). The photothermal conversion efficiencies (η) of FP-POP and iFP-POP based on eq S4 were calculated to be 27.16% and 29.36%, respectively. , The temperature changes of FP-POP (200 μg mL –1 ) and iFP-POP (200 μg mL –1 ) during three consecutive ramp-up and ramp-down processes (Figure h) were detected by controlling the laser on/off. No significant change was detected in the three consecutive cycles, implying good photothermal stability of the as-synthesized polymers.…”
Section: Resultsmentioning
confidence: 99%
“…The controlled concentration of the ions released, the particle size and shape, and the type of microorganism are important in this case. 37,63 The third most convincible antibacterial mechanism relates to the generation of cytotoxic ROS radicals under light irradiation that directly interacts with the cellular components of pathogens. This interaction causes oxidative damage to the antioxidant defense system, disrupts the lipid metabolism, cell proteins, and DNA of the cell membrane, and ultimately leads to the disruption of bacterial growth and proliferation.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Furthermore, pristine TiS 2 tends to agglomerate into bulk NPs during synthesis and displays an inert nature, limiting its interaction with microbes and consequently leading to poor antimicrobial efficiency . Previously, various strategies have been explored to enhance the antimicrobial behavior of pristine metal sulfides, for example, the synthesis of ultrasmall and thinner nanoarchitectures with suitable electronic band alignments, , employment of chemical doping or coating approaches, , and construction of effective heterogeneous structures with several carbonaceous matrixes, such as mesoporous/microporous carbons, carbon nanotubes, graphene, MXenes, and so on. It has been observed that reducing the size and layer thickness of the TMSs can increase their band gap due to the quantum confinement effect, resulting in a larger specific surface area, energetic electron–hole mobility, and shorter transportation distance and thus inevitably generating elevated levels of cytotoxic ROS in the resulting system. , These anticipated properties have been consistently observed in various studies by downsizing or making single- to few-layered structures. ,, For instance, Tian and colleagues demonstrated that smaller MoS 2 quantum dots with a band gap of approximately 1.8 eV exhibit a superior antimicrobial performance compared to bulk MoS 2 with a band gap of around 1.2 eV.…”
Section: Introductionmentioning
confidence: 99%